The Role of Sport Programs in Peace Building. Anthropological Study at El-Zhour Club in Cairo - Mostafa, Samah Ahmed Faried (European Scientific Journal, ESJ, 2018)
In Egypt, after leading change in the 2011 revolution, and being the majority of the Egyptian population, young Egyptians became the focus of much attention in the political and media speech. Sport for peace building has become an acknowledged policy in underprivileged communities both in the developing and developed world. The study argues that sport for peace programs in Egypt hold the potential role not only to alter structural violence but also to prevent the violence in the form of extremism. This study aims to place the perception of the sport importance and its influence’ on youth manner especially towards peace building and conflict resolution. It is important to reveal youth’ perception and their recommendations about peace and conflict after participating in some sports program at the club. The purpose of this paper is to determine the current barriers faced by Egyptian sport federations in their policy to reduce the social conflict. The data set is made up of youth and expert interviews, coaches and supplemented by ethnographic records about youth sport programs collected by the author through observation and scale. The methodology of the study is based on both the descriptive analytical method and a Likert Scale measurement. The results discovered the need of extra definitions and applications from the religious, art and cultural program beside the sports program to achieve the peace building. They suggested extra programs which may develop their character such as the development of cultural and social awareness.